2015
DOI: 10.2147/ijn.s72726
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blood protein adsorption on cellular uptake of anatase TiO2 nanoparticles

Abstract: Protein adsorption onto nanoparticles (NPs) in biological fluids has emerged as an important factor when testing biological responses to NPs, as this may influence both uptake and subsequent toxicity. The aim of the present study was to quantify the adsorption of proteins onto TiO 2 NPs and to test the influence on cellular uptake. The surface composition of the particles was characterized by thermal analysis and by X-ray photoelectron spectroscopy. The adsorption of three blood proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 59 publications
1
7
0
1
Order By: Relevance
“…In vivo , it was shown that proteins adsorb on TiO 2 NPs. In some cases, these NPs induced conformational changes in proteins and affected their functions [ 12 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , it was shown that proteins adsorb on TiO 2 NPs. In some cases, these NPs induced conformational changes in proteins and affected their functions [ 12 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…37 A recent experimental study showed that TiO 2 NPs adsorbed with blood proteins are less likely to be uptaken by cells. 39 Similarly, previous investigation on blood proteins adsorbed on CNTs also showed a reduced cytotoxicity of CNTs. Therefore, blood proteins can help on the clearance of entered NPs and provide an extra barrier for the cellular uptaken.…”
Section: The Human Serum Albumin Protein On the Nano-particlementioning
confidence: 70%
“…For example, the curvature of a NP can affect the protein adsorption, 39 which shows the size effect of NPs in a toxic process. With new force fields for TiO 2 NPs, many intriguing phenomena in experiment could be interpreted from MD simulations.…”
Section: Resultsmentioning
confidence: 99%
“…A disadvantage of these techniques is that there is no possibility to distinguish between NMs that are internalized into the cells, extracellularly associated and/or just located between cells or within the extracellular fluid 19. It has been shown that there is a significant difference between uptake measured by means of ICP‐MS and uptake based on the analysis of individual cells 17…”
Section: Label‐free Dosimetry and Imaging Techniques—toward High Thromentioning
confidence: 99%